The Effect of Ownership Concentration on the Earnings Quality: Evidence from Indonesian Companies - Rahmat Febrianto (The Indonesian Journal of Accounting Research, 2013)
Indonesian public corporations formerly were family-owned business. Since the legal protection of property rights by the state is still low, those families secure their assets by only emitted a small portion of stocks. Considering the high ownership concentration in public corporations and Indonesian cultures, the accounting information quality released is investigated.The result shows that market reacts negatively to the earnings information released by concentrated public companies. This result conforms to the entrenchment effect and gives evidence how minority owners react to earnings information released by majority owners. This study also uses firm specific regression method for sensitivity analysis.